Ag(i)-Catalyzed rapid access to 2-amino-4-methylenethiazolines with potential applications in bioconjugation chemistry. Issue 18 (16th April 2021) - Xiang, Lingling; Wu, Haiting; Liang, Yunshi; Deng, Huiying; He, Yiting; Xu, Qin; Zhang, Jing
Abstract : An Ag(i )-catalyzed synthesis of 2-amino-4-methylenethiazolines from isothiocyanate and propargylamine was developed, and its implication in bioconjugation was examined. Abstract : An Ag(i )-catalyzed tandem addition–cyclization of isothiocyanate and propargylamine was successfully applied to the synthesis of 2-amino-4-methylenethiazolines. This route features an unprecedented fast reaction rate with full conversion reached within 10 min at room temperature for aromatic isothiocyanates and excellent chemoselectivity for exocyclic products. The application of this strategy is further highlighted by the accelerated bioconjugation of propargylamine with fluorescein isothiocyanate (FITC) under Ag(i )-catalysis.